Analisis Produktivitas Produksi Body Scrub Di PT. XYZ - Tinambunan, Nurcahaya; Yoga, I Wayan Gede Sedana; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Productivity is an important indicator in assessing the efficiency and competitiveness of a company. PT XYZ, a SPA product production company established in 2000, experienced an annual decrease in productivity ranging from 1% to 5% during the 2019-2024 period. This decline is influenced by a variety of factors, with the increasing number of defective products being the main causative factor. This study aims to measure the productivity level of body scrub production, identify the causes of low productivity index, and provide recommendations for strategies to increase productivity. The Production, Organization, Sales, Product, Arbeiter, Capital (POSPAC) method is used to measure productivity levels; Fishbone diagrams to analyze the causes of the decline; and the Analytic Hierarchy Process (AHP) to determine the best solution. The results of the analysis show that the elements of production, sales, products, and capital experienced a significant decline during 2020–2024, with the highest decline in 2024 of 5.32%. The main factors that cause this include: high employee absenteeism, raw material inconsistency, broken machinery, less strict QC system, weak safety stock management. The recommended strategies include the implementation of incentive and monitoring systems, preventive maintenance, layered QC, standardization of material composition and moisture level analysis, as well as the formation of a Quality Assurance (QA)team.